Where Now? Current Observations, Future Directions. Issue 3 (May 2020) - Ferman, Barbara
In this final article, I sum up the major comments, respond to the questions, and address the critiques of the contributing authors. I also examine some key developments that occurred after the publication of the book, particularly the rash of teacher strikes in red states and the nationwide student movement against gun violence. What might these events portend for large-scale coalition building to preserve education as a public good?